Engaging university students : international insights from system-wide studies - McCormick, Alexander C. (Springer Singapore Imprint: Springer, 2014)
This book provides university teachers, leaders and policymakers with evidence on how researchers in several countries are monitoring and improving student engagement-the extent to which students are exposed to and participate in effective educational practices. It captures insights from international implementations of the National Survey of Student Engagement (NSSE), developed in the United States. In the last half decade NSSE has been adapted and used in several other countries, producing the largest international collaboration yet involving educationally relevant data on students' engagement in higher education. Leaders of established national collaborations draw on their experiences with hundreds of institutions to contribute their insights. Framed by their cultural and educational contexts, they discuss issues concerning first-year learners, international students, part-time and distance learners, as well as teaching and leadership in support of student learning. Each chapter outlines strategies based on national case studies and presents perspectives supported by concrete examples of how these have played out in diverse settings. The book suggests mechanisms that can be used by institutions, ministries and quality agencies around the world.